PENGARUH PERLAKUAN SERAT SABUK KELAPA (SSK)TERHADAP MORFOLOGI DAN SIFAT AKUSTIK KOMPOSIT BERPENGUAT SSK - Muslimin, Mukhlis; Umar, Kifli; Seng, Ahmad; Daud, Kadri; LM, Samsul Bahri (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
The research aims to determine the effect of SSK treatment with liquid smoke on the morphology and acoustic properties of SSK reinforced composites. The research method is an experimental method with variations in fiber treatment by soaking in liquid smoke for 1, 2 and 3 hours. Next, after soaking the fiber, it is heated in an oven at 40ºC for 30 minutes, then the resulting fiber morphology is observed using a JEOL JCM 6000 SEM tool then SSK reinforced composites are made for acoustic testing, specimen making is done by preparing resin and long fibers. 1 cm fiber, 60% resin composition and 40% SBP, after drying a composite acoustic test specimen was made. The results show that SSK treatment with liquid smoke increases the fiber morphology to become rough and porous, so that the SSK reinforced composite has a sound absorption coefficient value for the SSK TP composite of 0.1175 db, while the SSK P1J, P2J, and P3J composites have a sound absorption coefficient value of 0.1304, 0.1199, and 0.1181 db. , this shows that the SSK P1J composite is better in sound absorption by 10.92% when compared with SSK TP, so it can be recommended as an environmentally friendly acoustic material.